1990
DOI: 10.1080/00220671.1990.10885988
|View full text |Cite
|
Sign up to set email alerts
|

What Influences Learning? A Content Analysis of Review Literature

Abstract: This paper reported a comprehensive "meta-review" and synthesis of research on variables related to learning, including both cognitive and affective schooling outcomes. 1 A conceptual framework was developed encompassing 228 items related to school learning, organized a priori into 30 scales within six categories. Search and selection procedures yielded 179 selected handbook and annual review chapters, commissioned papers, and other authoritative reviews. Content analysis yielded over 3,700 ratings of the stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
175
0
32

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(240 citation statements)
references
References 32 publications
8
175
0
32
Order By: Relevance
“…In general, self-regulative activities, such as orientation, planning, monitoring, readjustment of strategies, evaluation and reflection, are found to be more typical of strong than poor learners (Wang et al, 1990). In a study on developing mathematical thinking and self-regulated learning, Pape et al (2003) stated that self-regulated learners are 'active participants in their own learning', are 'able to select from a repertoire of strategies' and 'able to monitor their progress in using these strategies towards a goal'.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 96%
“…In general, self-regulative activities, such as orientation, planning, monitoring, readjustment of strategies, evaluation and reflection, are found to be more typical of strong than poor learners (Wang et al, 1990). In a study on developing mathematical thinking and self-regulated learning, Pape et al (2003) stated that self-regulated learners are 'active participants in their own learning', are 'able to select from a repertoire of strategies' and 'able to monitor their progress in using these strategies towards a goal'.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 96%
“…Amali reported that language learners use the metacognition skills, including programming, self-review and self-evaluation, in order to facilitate their English language learning (Wang, 1990). …”
Section: The Concept Of Metacognitive Learningmentioning
confidence: 99%
“…1-Interest in lesson 2-Homework volume 3-Character 4-Self-concept, self-sufficient 5-Motivation and self-efficiency 6-Anxiety, enough or lack of enough facilities 7-Teacher skills and method of teaching (Wang, 1990) Identification of these factors helps with selection of proper methods and improvement of conditions for excitement of learners for learning. In between, features related to learners are the most important factors of need.…”
Section: Role Of Word Etymology In Language Learningmentioning
confidence: 99%
“…Les enseignants qui obtiennent le plus de succès dans la gestion de leur classe supervisent le déroulement des activités de près et sont capables de reconnaître rapidement, voire d'anticiper, les comportements indésirables susceptibles de se propager à l'ensemble du groupe et de perturber l'ordre établi (Butler, 1987;Doyle, 1986Doyle, , 1990Good, 1983Good, /* et b, 1990Tomic 1992;Wang, Haertel et Walberg, 1990). Ils savent prendre des mesures appropriées avant que le désordre n'apparaisse (Doyle, 1986(Doyle, , 1990Tomic, 1992) et ils disposent de procédures et de techniques variées permettant de contrôler ces situations (Cruickshank 1990;Doyle 1986Doyle , 1990Medley, 1977;Tomic 1992).…”
Section: La Gestion De La Classe En Situation D'interaction Avec Lesunclassified